Impact of elaboration on responding to situational judgment test items - LIEVENS, Filip (Institutional Knowledge at Singapore Management University, 2008)
Although faking has been identified as a potential problem in situational judgment tests (SJTs), no studies have investigated proactive approaches for controlling faking in SJTs. Therefore, this study examined the impact of elaboration on responding to SJT items. Elaboration was operationalized as reason-giving. Two hundred and forty-seven master students were assigned to either an honest or a fake condition, and to a non-elaboration or an elaboration condition. Results showed that elaboration decreased the effect of faking for items with high familiarity. Elaboration on familiar items also decreased the percentage of fakers in the top of the distribution. Next, participants in the elaboration condition rated the SJT significantly higher in terms of allowing them to present themselves more realistically and to demonstrate their knowledge, skills, and abilities. Finally, there were no significant differences in participants' satisfaction with the SJT across the elaboration and non-elaboration condition.